Numerical Investigation of Influences of Drilling Arrangements on the Mechanical Behavior and Energy Evolution of Coal Models - Tong-bin Zhao; Wei-yao Guo; Feng-hai Yu; Yun-liang Tan; Bin Huang; Shan-chao Hu (Advances in Civil Engineering)
Destress drilling method is one of the commonly used methods for mitigating rock bursts, especially in coal mining. To better understand the influences of drilling arrangements on the destress effect is beneficial for rock burst mitigation. This study first introduced the rock burst mitigation mechanism of the destress drilling method and then numerically investigated the influences of drilling arrangements on the mechanical properties of coal models through uniaxial compression tests. Based on the test results, the energy evolution (i.e., the energy dissipation and bursting energy indexes) influenced by different drilling arrangements was analyzed. When the drilling diameter, the number of drilling holes in one row, or the number of drilling rows increases, the bearing capacity of specimens nonlinearly decreases, but the energy dissipation index increases. In addition, the drilling diameter or the number of drilling holes in one row affects the failure mode weakly, which is different from that of the number of drilling rows. Consequently, the bursting energy index decreases as increasing the drilling diameter or the number of drilling holes in one row, but as increasing the number of drilling rows, the variation law of bursting energy index is not obvious. At last, the influencing mechanism of drilling arrangement on the rock burst prevention mechanism of the destress drilling method was discussed and revealed.